2014
DOI: 10.1002/app.41241
|View full text |Cite
|
Sign up to set email alerts
|

The effect of BMP‐2 and VEGF loading of gelatin‐pectin‐BCP scaffolds to enhance osteoblast proliferation

Abstract: A composite scaffold of gelatine (Gel)-pectin (Pec)-biphasic calcium phosphate (BCP) was successfully fabricated. Growth factors such as bone morphogenetic protein-2 (BMP-2) and vascular endothelial growth factor (VEGF) were loaded into the Gel-Pec-BCP hydrogel scaffolds by freeze-drying. The surface morphology was investigated by scanning electron microscopy, and BCP dispersion in the hydrogel scaffolds was measured by energy dispersive and X-ray diffraction spectroscopy. The results obtained from Fourier tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…The sustained release may be attributed to the electrical interaction between the positively charged amino acid residues in the VEGF proteins, and the negatively charged sites of the pectin, FG. The release profi les of VEGF from FG also confi rmed the strong interaction which was similar with previous study 45) . The results indicated that the VEGF protein was released from the fi brin clots more slowly, and this fi nding was in agreement with previous studies using diff erent types of delivery system 46,47) .…”
Section: Discussionsupporting
confidence: 90%
“…The sustained release may be attributed to the electrical interaction between the positively charged amino acid residues in the VEGF proteins, and the negatively charged sites of the pectin, FG. The release profi les of VEGF from FG also confi rmed the strong interaction which was similar with previous study 45) . The results indicated that the VEGF protein was released from the fi brin clots more slowly, and this fi nding was in agreement with previous studies using diff erent types of delivery system 46,47) .…”
Section: Discussionsupporting
confidence: 90%
“…Jung et al . (2013) have demonstrated that BMP‐2 loaded in Col exhibits the best release with almost 70% of BMP‐2 being released during the 2nd day . Brown et al .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that different types of polymer and ceramics used in composite scaffold have different drug or growth factor release profiles . In fact, incorporation of some bioceramic nanopowder such as HAp and BCP into polymeric matrix can increase drug integrity result in the sustain release of immobilized or incorporated drug from composite scaffold . In addition to, the sustain release in the polymeric and composite system can attributed to positive charge of BMP‐2 amino acid and negative charge of polymer(negative charge) and bioceramics such as BCP and HAp .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin is derived from high molecular weight collagen by breaking the natural triple-helix structure of collagen into single-stranded molecules; it has been used in many aspects of tissue engineering because of its biocompatibility and ease of gelation [18]. Due to the loosened structure of the biopolymer skeleton, gelatin can easily spread across and over the scaffold surface.…”
Section: Introductionmentioning
confidence: 99%